Teaching writing in large classes through peer tutoring in university of economic and technical industries - Nguyen, Thi Ngoc Anh (University of Foreign Languages and International studies, 2017)
This study was carry out to investigate (1) current situations of use of peer tutoring in large writing classes (2) advantages of use of peer tutoring in large writing classes and ( 3) difficulties of use of peer tutoring in large writing classes. 250 stud (...)